2016
DOI: 10.1016/j.dhjo.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy among women with physical disabilities: Unmet needs and recommendations on navigating pregnancy

Abstract: Background Despite concerns raised in the literature on the adverse pregnancy outcomes of women with physical disabilities, there is little information about unmet needs of women with physical disabilities during pregnancy and childbirth. Objective This article provides an in-depth examination of unmet healthcare needs during and around the time of pregnancy among a sample of women with physical disabilities. It also offers recommendations to other women with physical disabilities who are considering pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 17 publications
4
85
0
14
Order By: Relevance
“…[2][3][4][5][6][7][8][9] Additionally, multiple providers noted that elderly patients appreciated how the tables could be adjusted. Similarly, providers noted that the width of the tables was conducive to examining obese patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9] Additionally, multiple providers noted that elderly patients appreciated how the tables could be adjusted. Similarly, providers noted that the width of the tables was conducive to examining obese patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[2][3][4] Lack of adequate accessible equipment can result in fewer preventive screenings and routine visits, delay care, and worsen health outcomes for PWD compared to persons without disability. [5][6][7][8][9] Story and colleagues found that when PWD access care, difficulties such as lack of physical support to transfer onto tables can negatively impact healthcare encounters. 10 These barriers are often compounded for certain disabled populations, including those with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Women with physical disabilities (WWPD) reported negative attitudes toward them from acquaintances as well as strangers (Iezzoni, Wint, Smeltzer, & Ecker, 2015a; Nosek, Rintala, Howland, Foley, & Bennett, 1995). They have also reported negative attitudes to their pregnancy on the part of health care clinicians and lack of knowledge about their needs related to pregnancy (Begley et al, 2009; Mitra et al, 2016b; Nosek et al, 1995). Women with disabilities have described inaccessible health care settings, including hospital rooms and clinical offices, and absence of adjustable tables and scales needed to obtain weights if they have limited mobility or are wheelchair users (Iezzoni, Wint, Smeltzer & Ecker, 2015b).…”
mentioning
confidence: 99%
“…Women with disabilities have described inaccessible health care settings, including hospital rooms and clinical offices, and absence of adjustable tables and scales needed to obtain weights if they have limited mobility or are wheelchair users (Iezzoni, Wint, Smeltzer & Ecker, 2015b). Additional issues identified by WWPD include their need for information about the interaction of their disability and pregnancy, and for knowledgeable health care clinicians who are sensitive to their needs and respectful of their desire to become parents (Mitra et al, 2016b; Smeltzer, 2007a). …”
mentioning
confidence: 99%
See 1 more Smart Citation